2013
DOI: 10.1007/s12275-013-3291-6
|View full text |Cite
|
Sign up to set email alerts
|

Penicillium daejeonium sp. nov., a new species isolated from a grape and schisandra fruit in Korea

Abstract: Two isolates of monoverticillate Penicillium species were collected from a grape and schisandra fruit in Korea. Multigene phylogenetic analyses with the nuclear ribosomal internal transcribed spacer (ITS) region and genes encoding β-tubulin (benA) and calmodulin (cmd), as well as morphological analyses revealed that the two isolates are members of the P. sclerotiorum complex in Penicillium subgenus Aspergilloides, but different from species of the P. sclerotiorum complex. The isolates are closely related to P.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…To date, seven species in section Sclerotiora have been reported in Korea: P. adametzioides, P. cainii , P. daejeonium , P. herquei , and P. sclerotiorum from terrestrial environments [17,18,25,26] and P. bilaiae and P. viticola from marine environments [12,13]. Through this study, we found eight species from marine environments.…”
Section: Resultsmentioning
confidence: 71%
See 1 more Smart Citation
“…To date, seven species in section Sclerotiora have been reported in Korea: P. adametzioides, P. cainii , P. daejeonium , P. herquei , and P. sclerotiorum from terrestrial environments [17,18,25,26] and P. bilaiae and P. viticola from marine environments [12,13]. Through this study, we found eight species from marine environments.…”
Section: Resultsmentioning
confidence: 71%
“…Currently, 30 species have been described in this section [21–24]. In Korea, seven species have been reported: five species from terrestrial environments [17,18,25,26] and two from marine environments [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…KC354569). Species of Penicillium exist in a wide range of habitats, and some Penicillium species often cause decay in postharvest fruits such as grape, apple, and citrus, even producing mycotoxins that contaminate juices and sauces from both healthy and partially rotten fruits (Sang et al, ). However, no data are available in the literature about the isolation of Penicillium sp.…”
Section: Resultsmentioning
confidence: 99%
“…Some of the new species discovered in Korea were isolated from various environmental samples such as P. daejeonium from grape and Schisandra fruit, P. koreense from soil, P. samsonianum from stems and leaves of Viscum album var. coloratum , P. jejuense from marine environments of Jeju Island, P. punicae from pomegranate ( Punica granatum ) fruit, P. aquaticum and P. acidum from freshwater [16,19–22]. Section Citrina represents one of these sections clade and are abundant worldwide [23].…”
Section: Introductionmentioning
confidence: 99%